Semiotics and Marian iconography in clothing images: case studies - Fernández De Alarcón Roca, Belén; Sánchez Hernández, María F. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of this study is to highlight the importance of Marian clothing images and the jewels and accessories they exhibit. The basis and key points of a nonverbal language acting as testimony of devotion, as well as the current social and economic relations that affect them, will be discussed. Based on the cases analysed, it will be demonstrated how the popular piety and the people and of the local cultures, are very often linked to certain events in the area. The results will demonstrate the importance given and values attributed to this type of iconography.